Ergonomic Evaluation of Improved Sickles in Wheat Harvesting - Dilbaghi, M; Gandhi, S; Bimla, Bimla (Journal of Agricultural Engineering, 2008)
Wheat harvesting is one of the important farm activity predominantly performed by rural women in Haryana. During harvesting season, they spend nearly 8-9 h daily to perform the activity. The aim of present study was to evaluate the performance of improved sickle over conventional sickle in terms of output and reduced drudgery. Experiment was conducted on 20 rural women aging 25-45 years of age with four sickles comprising one conventional sickle (S0) and three improved sickles viz., S1, S2 and S3. S0 sickle Was the heaviest measuring 234 g followed by S2 (217 g) and S3 (198 g). S1 sickle was the lightest in weight (186 g). Blades of all the improved sickles were made up of high carbon steel except for conventional sickle that was made up of iron. In terms of physical fitness index, two-fifth of the respondents had high average PFI whereas 40% had good PH Output was found maximum for S2 sickle (64.9 kg). S2 sickle resulted 4.8% more out put over conventional sickle resulting 16.4% increase in area covered. Average working heart rate (107 bpm) and corresponding energy expenditure (8.37 KJ/min) was found minimum for S2 sickle. Total cardiac cost of work for all the sickles ranged from 1020 beats to 1283 beats. Reduction in TCCW of improved sickles over conventional (S0) sickle was maximum for S2 (20.5%) followed by S1 (20.4%). S2 sickle resulted in minimum grip fatigue after the activity (3.8%). Regarding musculo-skeletal discomforts, maximum reduction in pain was reported in thighs (43.3%) followed by wrist joint (42.3%), shoulder joint (41.8%), feet (33.5%) and neck (30%).